A Competency-Based Approach to Developing Students' Listening and Reading Skills While Foreign Language Learning - Anataichuk, Inna M.; Zabrudska, Lіudmyla М.; Sazonova, Viktoriia S. (Bulletin of Science and Education, 2025)
ENG: The competence-based approach to foreign language learning involves not only the development of linguistic knowledge (vocabulary, grammar, phonetics) but also the ability to use this knowledge effectively in real-life situations. This means that the primary focus is on the practical aspect of language proficiency, which ensures not only the acquisition of theoretical material but also the development of language skills, intercultural communication abilities, critical thinking, teamwork, and problem-solving competencies. A particular emphasis is placed on listening and reading skills, as they serve as the foundation for receiving, processing, and analyzing information and for the further development of other types of language activities such as speaking and writing.The aim of this article is to define the main principles of the competence-based approach to developing students’ listening and reading skills and to identify the key challenges associated with its implementation in the educational process. The study analyzes both didactic and psychological aspects of language teaching and explores effective strategies and methodologies that enhance active student participation. This approach transforms learning from passive knowledge absorption into an active process where students become full participants in communication and knowledge acquisition.The competence-based approach is also closely linked to increased student motivation. Learners see the practical benefits of studying the language, as the acquired knowledge and skills enable them to navigate in a foreign-language environment, comprehend authentic texts, and participate in intercultural dialogue. The use of interactive teaching methods, authentic materials, and situational modeling creates favorable conditions for the effective development of listening and reading skills, as well as for the formation of key competencies required in modern society.

UKR: Компетентнісний підхід до вивчення іноземної мови передбачає розвиток не лише лінгвістичних знань (лексики, граматики, фонетики), а й формування здатності ефективно використовувати ці знання у реальних життєвих ситуаціях. Це означає, що основна увага приділяється практичному аспекту володіння мовою, який забезпечує не лише засвоєння теоретичного матеріалу, але й розвиток мовленнєвих навичок, здатності до міжкультурної комунікації, критичного мислення, уміння працювати в команді та вирішувати проблеми. Особливу роль у цьому процесі відіграють навички аудіювання та читання, оскільки саме вони є базою для отримання, обробки та аналізу інформації, а також для подальшого формування інших видів мовленнєвої діяльності, зокрема говоріння та письма.Мета статті – визначити основні принципи компетентнісного підходу до розвитку навичок аудіювання та читання у студентів, а також виявити ключові труднощі, що виникають під час його впровадження в освітній процес. У рамках дослідження аналізуються дидактичні та психологічні аспекти навчання, розглядаються ефективні стратегії та методики, які сприяють активному залученню студентів до навчального процесу. Такий підхід дає змогу перетворити навчання з пасивного засвоєння матеріалу на активну діяльність, у якій студенти стають повноцінними учасниками комунікації та здобувачами знань.Компетентнісний підхід також тісно пов’язаний із підвищенням мотивації студентів. Вони бачать практичну користь від вивчення мови, адже здобуті знання та вміння дозволяють їм орієнтуватися в іншомовному середовищі, сприймати автентичні тексти, брати участь у міжкультурному діалозі. Застосування інтерактивних методів навчання, автентичних матеріалів та ситуаційного моделювання створює умови для ефективного розвитку навичок аудіювання та читання, а також формування ключових компетентностей, необхідних у сучасному суспільстві.
Компетентнісний підхід до розвитку у студентів навичок аудіювання та читання під час вивчення іноземної мови
Inna M.Anataichuk: ORCID 0000-0001-5264-1262; Lіudmyla М.Zabrudska: ORCID 0000-0001-5564-8638; Viktoriia S.Sazonova: ORCID 0000-0003-1332-6109
Keywords: competencies; communication; reading skills; listening skills; approach; компетентності; комунікація; навички читання; навички аудіювання; підхід; КФП; TECHNOLOGY; NATURAL SCIENCES; NATURAL SCIENCES:: Сommunication; NATURAL SCIENCES:: Сommunication:: Аpproach